Prevalence and risk factors of anemia in under five-year-old children in children’s hospital - ., Kanchana; Sr., Madhusudan; Ahuja, Sam; Nagaraj, Niranjan (International Journal of Contemporary Pediatrics, 2018)
Background: Anemia is a global public health problem affecting both developing and developed countries with major consequences for human health as well as social and economic development. This study is conducted to assess the proportion of children, aged between 6 months to 5 years having anemia and risk factors of iron deficiency anemia among selected children with anemia. Methods: The present cross-sectional study was conducted in 500 children between the age of 6 months to 5 years, who were admitted (in patients) to the Department of Pediatrics of Dr. BR Ambedkar Medical College, Bangalore, were selected and screened for anemia by hemoglobin estimation. This study was carried out from November 2012 to April 2014. Among those children with hemoglobin <11 g/dl, were screened for iron deficiency anemia (Serum ferritin estimation is done). Among these 500 children, 100 children with a hemoglobin level of 11 gm/dl and serum ferritin <12 μg/L were taken up for detailed study. All the collected data was tabulated and statically analysed by using appropriate methods Results: 77.8% of screened children were found to have anemia. In studied children 38% had mild anemia, 54% had moderate anemia and 8% had severe anemia. Male outnumbered than female in the ratio of 1.17:1. More than 50% presented with acute gastroenteritis.79% of anemic children had malnutrition. 24% of anemic children were low birth weight. Dimorphic anemia was common in 6months to 5 years age group. Mean hemoglobin level was 9.26. Mean ferritin, mean serum iron, TIBC, transferrin saturation was 7.23 μg/l, 52.60μg/dl, 346.89mg/dl and 16.31% respectively Conclusions: The diet deficient in iron and other essential nutrients is the single most important cause of anemia in children of this age Diarrhea was the chief associated symptom in more than half the cases studied. Hence it is essential to make provision for safe drinking water and to improve sanitary facilities periodic deworming measure is advised, to reduce parasitic infestation which also contributes to the development of anemia.